Kontrollhely Magyarországon: Egy reprezentatív felmérés eredményei - Róbert Károlyi; Hubert János Kiss; Ágnes Szabó-Morvai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
– In our study, we present the concept of locus of control, a non-cognitive ability that is increasingly researched in economics. We then review the economic literature on locus of control and show that people who believe they are in control of their lives are more successful in many areas of life. After that, we examine the data of a representative Hungarian survey, in which we mostly see the correlations revealed by the literature. The locus of control becomes more and more internal in the respondents' 20s and 30s, and then becomes more and more external again after the age of 40. In our sample, men on average have a more internal locus of control than women, and a more internal locus of control is associated with higher education and higher income. At the same time, we do not find a significant correlation between locus of control and labor market status. We find that those with more internal locus of control accumulate significantly more savings and less debt.
Keywords: D01; D14; D91; 330; locus of control; education; income; finances